On the Time Variable Rotation Measure in the Core Region of Markarian 421 - Rocco Lico; José L. Gómez; Keiichi Asada; Antonio Fuentes (Galaxies, 2017)
In this conference contribution, we discuss and interpret the time variable rotation measure (RM) detected in the core region of the TeV blazar Markarian 421 (Mrk 421). We monitored Mrk 421 during 2011 with one observing run per month at 15, 24, and 43 GHz with the American Very Long Baseline Array. We explore the possible connection between the RM and the accretion rate, and we investigate the Faraday screen properties and its location with respect to the jet emitting region. Among the various scenarios, the jet sheath is the most promising candidate for being the main source of Faraday rotation. We interpret the RM sign reversals observed during the one-year monitoring within the context of the magnetic tower models by invoking the presence of two nested helical magnetic fields in the relativistic jet with opposite helicities, originating through the Poynting–Robertson cosmic battery effect. The net observed RM values result from the relative contribution of both inner and outer helical fields.